Simbolisasi Etnik Muna di Bandung: Studi Identitas Etnik Orang Muna - Sumadi Dila (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2008)
The important thing of openness attitude, tolerance and communication skill that are different in cultural at urban complex community is the successful key to make closer living in harmony side by side. This research is aimed to understant and to explain yhe interaction and the communication of Muna people in relating with their ethnic identity in cociety in Bandung. The result of research finds the constuction mechanism of Muna ethnic identity through the self strengthening, evaluation, dialogue, adaptation, and structuring that form Muna ethnic categiries of Regionalism, Prgmatic,and Religious. This research also find the accentuation of symbols, setting, and ethnic identity using in expressive and impressive manner based on personality (individual) and social. The identity of regionalism Muna ethnic as the past self consept is’n dominant anymore, on the contrary the identity of pragmatic Muna and relgious Muna ethnic are showed more often as the present self concept based on new situation. That’s done to complete the self adaptation in fostering the community awareness and acceptance.